2012
DOI: 10.12659/ajcr.883382
|View full text |Cite
|
Sign up to set email alerts
|

A case of synchronous double primary breast carcinoma and osteosarcoma: Mismatch repair genes mutations as a possible cause for multiple early onset malignant tumors

Abstract: SummaryBackground:Simultaneous or consequent development of multiple solid tumors might be faced in some patients, especially the young. These tumors might be related to certain hereditary cancer syndromes or certain genetic predispositions.Case Report:We present the case of a 19-year-old woman with metastatic breast cancer to the contralateral axillary lymph node, associated with simultaneous osteosarcoma of the left lower femur. As she did not fit into any of the familial cancer syndromes, genetic predisposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It forms a heterodimer with MSH6 or MSH3 to form the DNA repair complex. A previous study demonstrated that MSH2 promotes methylation, microsatellite instability and various mutational events associated with development of OS (42). It also distinguishes OS cancer stem cells from normal cells by mediating DNA repair (43).…”
Section: Discussionmentioning
confidence: 99%
“…It forms a heterodimer with MSH6 or MSH3 to form the DNA repair complex. A previous study demonstrated that MSH2 promotes methylation, microsatellite instability and various mutational events associated with development of OS (42). It also distinguishes OS cancer stem cells from normal cells by mediating DNA repair (43).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that upregulating cyclin D1 could suppress OS cell growth, metastasis, and apoptosis as an important signaling arm required for maximizing the mediator complex subunit 19 (Med19; Yu et al, 2014). There was a high expression of PCNA observed in the OS cell nucleus and cytoplasm (Wang, Luo, & Wang, 2006 (Ahmed et al, 2012). Another study has previously proven to us that c-myc could positively modulate MMR activity (Partlin et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…More so, Jentzsch et al showed us that the MSH6 gene mutations could result in deficiencies in DNA MMR proteins (Jentzsch et al, ). Moreover, it has also been proven that a decreased expression of MSH6 is linked with longer OS cell survival times (Ahmed, Salama, Salem, & Bahnassy, ). Unfortunately, it is still unknown whether or not MSH6 gene silencing may have the same function with MSH6 genes mutations and whether it, when combined with DDP, will have the better inhibitory effect to OS cells.…”
Section: Introductionmentioning
confidence: 99%
“…Current opinions agree that the metastasis of osteosarcoma is a complex process involving multiple factors in a cascade, accompanying with the higher metastatic activity of tumor cells. Previous studies have indicated the participation of certain genes in the metastasis of osteosarcoma and named them osteosarcoma metastasis-related genes [ 18 20 ]. Therefore it is of critical values for the treatment against osteosarcoma to identify and confirm such genes, in addition to the functional characterization of their roles in the occurrence, progression and prognosis prediction [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%